Peran Evaluasi Kinerja Dalam Organisasi - Bara Jonathan Rihi Hina; Sri Sundari; Marisi Pakpahan (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
This research aims to identify the role of performance evaluation in organizations. The focus of this research is to understand how implementing a good performance evaluation system can have a positive impact on the organization. This research method focuses on critical analysis of scientific literature, case studies, and expert views in the field of human resource management. Using this approach, this research involves synthesizing information from various sources to construct a comprehensive understanding of how performance evaluation can be a catalyst in organizational development. The results of this research outline the importance of implementing performance evaluation as a strategic tool for identifying employee strengths and weaknesses, as well as designing programs employee development as an important strategy in organizational development.